Implikasi Pelanggaran Privasi Anak dalam Bermedia Sosial Terhadap Kesehatan Mental di Sekolah Dasar - Rahmadani, Nafa Della; Lestari, Sruni Rama; Astuti, Rina Windah (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2024)
This research aims to analyze the implications of violating children's privacy in using social media on mental health in elementary schools. The research method uses a qualitative descriptive approach, with research subjects selected through purposive sampling from elementary school students who actively use social media. Data was collected through observations and in-depth interviews with parents, teachers and students to understand their experiences regarding social media use and its impact on mental health. Data analysis was carried out by identifying the main patterns and themes that emerged from the results of observations and interviews. The conclusions of this study indicate that privacy violations on social media have a significant negative impact on children's mental health, including anxiety, depression, and decreased self-confidence. Cooperation between parents, teachers and authorities is necessary to protect children's privacy and their mental health.